More social species live longer, have longer generation times, and longer reproductive windows - Salguero-Gomez, R (Royal Society, 2024)
The role of sociality in the demography of animals has become an intense focus of research in recent decades. However, efforts to understand the sociality-demography nexus have focused on single species or isolated taxonomic groups. Consequently, we lack generality regarding how sociality associates with demographic traits within the Animal Kingdom. Here, I propose a continuum of sociality, from solitary to tightly social, and test whether this continuum correlates with the key demographic properties of 152 species, from jellyfish to humans. After correction for body mass and phylogenetic relationships, I show that the sociality continuum is associated with key life history traits: more social species live longer, postpone maturity, have longer generation time, and greater probability of achieving reproduction than solitary, gregarious, communal, or colonial species. Contrary to the social buffering hypothesis, sociality does not result in more buffered populations. While more social species have a lower ability to benefit from disturbances, they display greater resistance than more solitary species. Finally, I also show that sociality does not shape reproductive or actuarial senescence rates. This cross-taxonomic examination of sociality across the demography of 13 taxonomic classes highlights keyways in which individual interactions shape most aspects of animal demography.